1998
DOI: 10.1017/s0043887100008121
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Foreign Aid Puzzle: A Comparison of American, Japanese, French, and Swedish Aid Flows

Abstract: This study explores the donor side of debates revolving around the proper role of foreign assistance as a foreign policy tool, by empirically testing for the aid determinants of four industrial democracies: France, Japan, Sweden, and the United States. A pooled cross-sectional time-series design is employed to assess the impacts of six sets of variables on aidflowsto thirty-six African states during the 1980s. Three sets of these variables—humanitarian need, strategic importance, and economic potential—are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
252
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(260 citation statements)
references
References 11 publications
3
252
0
1
Order By: Relevance
“…Apart from altruistic motivations of aid, Schraeder et al (1998) Alesina and Dollar (2000) as well as Gates and Hoeffler (2004) find the same pattern also for the other G7 countries.…”
Section: Previous Literaturementioning
confidence: 60%
See 1 more Smart Citation
“…Apart from altruistic motivations of aid, Schraeder et al (1998) Alesina and Dollar (2000) as well as Gates and Hoeffler (2004) find the same pattern also for the other G7 countries.…”
Section: Previous Literaturementioning
confidence: 60%
“…Research conducted in the 1970s and 1980s, summarized by McGillivray (2003), revealed that bilateral donors largely pursued their own interests when allocating aid across recipients. The rhetoric of donors is also in conflict with more recent empirical studies such as Schraeder et al (1998), Alesina and Dollar (2000), Alesina and Weder (2002), and Collier and Dollar (2002).…”
Section: Introductionmentioning
confidence: 94%
“…In essence, aid supply is made contingent on the willingness of recipient countries to bow to conditions and political motivations of donor countries. Accordingly, the political economy perspective of development assistance is crucially relevant in understanding the results because the motives of aid are products of institutions, culture, dynamics of competitive interest and power distribution (Schraeder et al, 1998;Hopkins, 2000;Asongu, 2014a). Development assistance is also the result of bargaining in some type of political market that consists of donor aid bureaucracies, recipient government officials and multilateral aid agencies.…”
Section: Further Discussion Policy Implications and Caveatsmentioning
confidence: 99%
“…To answer these questions, we will borrow from the theoretical framework used in the aid allocation literature. Ever since McKinlay and Little (1977), it has become common in this literature to distinguish between factors of donor interest and recipient need, both of which are expected to influence the allocation of aid to developing countries (see, for example, Trumbull and Wall, 1994;Schraeder, Hook and Taylor, 1998;Alesina and Dollar, 2000). What is less commonly known is that McKinlay and Little already tested for the role of what they called 'political stability and democracy' on aid allocation.…”
Section: Determinants Of Bit Schedulingmentioning
confidence: 99%